Human dietary exposure to bisphenol-diglycidyl ethers in China: Comprehensive assessment through a total diet study. (December 2022) - Li, Hui; Li, Heli; Wu, Xuan; Wu, Yige; Zhang, Jing; Niu, Yumin; Wu, Yongning; Li, Jingguang; Zhao, Yunfeng; Lyu, Bing; Shao, Bing
Highlights: A China total diet study on exposure to nine BDGEs was comprehensively assessed. BADGE and BADGE·2H2 O is exposure of greater concern compared to BFDGEs. Meats, eggs, and aquatic products are the main source of dietary exposure. Current BDGEs exposure levels do not pose risks to general population. Abstract: Despite the widespread use of bisphenol A diglycidyl ether (BADGE) and bisphenol F diglycidyl ether (BFDGE) in various consumer products as protective plasticizer, studies on human dietary exposure to these compounds are scare. In this study, nine bisphenol diglycidyl ethers (BDGEs) including BADGE, BFDGE, and seven of their derivatives were determined in the Chinese adult population based on composite dietary samples collected from the sixth (2016–2019) China total diet study (TDS). Contamination level of nine BDGEs was determined in 288 composite dietary samples from 24 provinces in China. BADGE·2H2 O and BADGE are the most frequently detected and BADGE·2H2 O presented the highest mean concentration (2.402 μg/kg). The most contaminated food composite is meats, with a mean ∑ 9 B D G E s of 8.203 μg/kg, followed by aquatic products (4.255 μg/kg), eggs (4.045 μg/kg), and dairy products (3.256 μg/kg). The estimated daily intake (EDI) of ∑ 9 B D G E s based on the mean and 95th percentile concentrations are 121.27 ng/kg bw/day and 249.71 ng/kg bw/day. Meats, eggs, and aquatic products are the main source of dietary exposure. Notably, beverages and water, alcohols were the main contributors of dietary exposure to BADGE and BADGE·2H2 O, followed by animal-derived foods. Dietary exposure assessment demonstrated that human dietary BDGEs do not pose risks to general population based on the mean and 95th percentile hazard index with < 1. This is the first comprehensive national dietary exposure assessment of BDGEs in Chinese general population.